Culture-Based Discovery Learning and its Impact on Mathematical Critical Thinking Skills - Ady Akbar; Tatang Herman; Didi Suryadi (Universitas Pendidikan Ganesha, 2023)
Complex life patterns in the 21st century require humans to master certain competencies and skills to adapt to life. Critical thinking ability is one of the important abilities to be mastered by today's students. This study aims to analyze the influence of culture-based discovery learning model learning. This type of research is quasi-experimental research. A total of 55 elementary schools and fifth-grade students were involved in this study. The experimental class consisting of 27 students was given treatment in the form of culture-based discovery learning, while the control class, which consisted of 28 students, was given conventional learning. Research data collection was carried out by giving tests of critical thinking skills in mathematics to two post-learning classes. Data analysis was carried out through descriptive data analysis and inference analysis through two independent sample t-tests with a significance level of 5%. The results showed significant differences in critical thinking skills between students taught through the culture-based discovery learning model and those taught through conventional learning models. The average critical thinking ability of students taught through the culture-based discovery learning model is higher than that of students taught through conventional learning models. It was concluded that the application of culture-based discovery learning can improve the critical thinking skills of elementary school students.